Do Board Gender Quotas Benefit Minority Shareholders? An Illustration through Related‐Party Transactions. (20th January 2021) - Nekhili, Mehdi; Bennouri, Moez; Nagati, Haithem
Abstract: We use a sample of French firms over the period 2001–2017 to investigate the relationship between board gender diversity and related‐party transactions (RPTs). Although some of these transactions are efficient, RPTs are usually perceived negatively by outsiders because of the existence of conflict‐of‐interest transactions deemed to be value‐destroying. Based on agency theory and managerial power theory, we argue that female directors have the ability and motivation to challenge managers' use of RPTs. Consistently with this argument, we find that board gender diversity negatively correlates with the number of reported RPTs. This negative correlation is driven by female directors involved in the board's monitoring duties (female independent directors and members of the audit committee). However, because they are less likely to be able to challenge managers, female inside directors do not affect the occurrence of RPTs. In January 2011, the French regulator enacted a gender quota law resulting in a significant increase in female board representativeness. We find that the marginal effect after enacting the gender quota law on the number of reported RPTs is negative for the proportion of female independent directors and female audit committee members, and positive for female inside directors.